2009
DOI: 10.1159/000233256
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Promote Oligodendroglial Differentiation in Hippocampal Slice Cultures

Abstract: We have previously shown that soluble factors derived from mesenchymal stem cells (MSCs) induce oligodendrogenic fate and differentiation in adult rat neural progenitors (NPCs) in vitro. Here, we investigated if this pro-oligodendrogenic effect is maintained after cells have been transplanted onto rat hippocampal slice cultures, a CNS-organotypic environment. We first tested whether NPCs, that were pre-differentiated in vitro by MSC-derived conditioned medium, would generate oligodendrocytes after transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…This study showed that MSCs enhanced OPC migration and maturation into oligodendrocytes promoting myelination in the corpus callosum. Consistent with this study, we have shown that ex vivo co-transplantation of MSCs together with NPCs onto hippocampal slice cultures (free of immune derived cells) induces NPCs to acquire an oligodendrocytic phenotype, while NPCs transplanted alone generated mostly astrocytes (Rivera et al, 2009). Regarding the underlying mechanisms, we have studied the eff ects of MSCs on NPCs in vitro and demonstrated that soluble factors present in MSC-CM strongly activate oligodendrogenesis in postmitotic NPCs (Rivera et al, 2006b).…”
Section: Transplanted Mscs Induce Neuroprotection and Enhance Cns Remsupporting
confidence: 66%
“…This study showed that MSCs enhanced OPC migration and maturation into oligodendrocytes promoting myelination in the corpus callosum. Consistent with this study, we have shown that ex vivo co-transplantation of MSCs together with NPCs onto hippocampal slice cultures (free of immune derived cells) induces NPCs to acquire an oligodendrocytic phenotype, while NPCs transplanted alone generated mostly astrocytes (Rivera et al, 2009). Regarding the underlying mechanisms, we have studied the eff ects of MSCs on NPCs in vitro and demonstrated that soluble factors present in MSC-CM strongly activate oligodendrogenesis in postmitotic NPCs (Rivera et al, 2006b).…”
Section: Transplanted Mscs Induce Neuroprotection and Enhance Cns Remsupporting
confidence: 66%
“…Moreover, we demonstrated that MSCs promote oligodendroglial differentiation of NPCs that were co-transplanted into a hippocampal slice [23]. Thus, factors derived from MSCs strongly promote oligodendrogenesis of differentiating cells.…”
Section: Introductionmentioning
confidence: 75%
“…Consistent with our previous in vitro observations, significantly fewer transplanted NSCs expressed GFAP protein when p57kip2 was suppressed prior to transplantation. These modulated cells showed a significant induction of the oligodendroglial precursor marker GST- (Rivera et al, 2009) and tended to induce expression of the oligodendroglial marker CC1 [ Fig. 7A; representative pictures of injection site in the white matter (ISWM) shown in Fig.…”
Section: Transplantation Of P57kip2 Suppressed Stem Cellsmentioning
confidence: 99%